Correction of hyperpigmented palmar grafts with full-thickness skin grafts from the lateral aspect of the foot. Issue 5 (October 2013) - Eryilmaz, Tolga; Tellioglu, Ali Teoman; Ozakpinar, Hulda Rifat; Oktem, Huseyin Fatih; Sen, Tulin; Albayrak, Aynur; Alper, Murat
Abstract The palmar surface of the hand possesses special features when compared with the hair-bearing parts of the body. The same quality of skin has to be used in reconstruction of the palmar skin defects to restore normal function. The lateral aspect of the foot has similar features with the palmar region histologically and can be used for palmar reconstruction. Seventeen patients who had hyperpigmentation after skin graft in the palmar region were treated. Scar contracture was combined in seven patients. The hyperpigmented grafts were excised and then the defects were full-thickness skin grafted from the lateral aspect of the foot. The mean follow-up period was 13.7 (4–22) months. Engraftment was successful in 16 patients, but one failed due to haematoma. The colour of the graft was initially reddish, and then became similar to the palmar area. The donor site healed without any problem within 3 weeks. At follow-up these grafts had good colour and texture match with adjacent palmar skin. There was no hyperpigmentation. Minimal marginal scarring and scar hypertrophy occurred in four patients (24%). The skin of the lateral aspect of the foot is a good choice for palmar skin defects, because of the similarities in their characteristics. Results are acceptable in terms of minimal recurrence of scar contracture, no hyperpigmentation, adequate colour and texture match, and minimal marginal scarring and scar hypertrophy.